Diaphorina citri populations carrying the bacterial plant pathogen Candidatus Liberibacter asiaticus are more susceptible to infection by entomopathogenic fungi than bacteria‐free populations. (14th October 2015) - Orduño‐Cruz, Nuvia; Guzmán‐Franco, Ariel W.; Rodríguez‐Leyva, Esteban
Abstract: The presence of Candidatus Liberibacter asiaticus (CLas) modifies the susceptibility of Diaphorina citri to fungal infection. Using one isolate of each the fungal species Beauveria bassiana, Metarhizium anisopliae and Isaria fumosorosea, we first estimated the LC50 for CLas‐free adults of D. citri . The lowest LC50 (1 × 10 4 conidia/mL) value was used to inoculate CLas‐free and CLas‐carrying adults of D. citri and their relative susceptibility was compared. CLas‐carrying adults were more susceptible than CLas‐free adults of D. citri to all three fungal isolates. The possibility of CLas exploiting D. citri as an alternative host, therefore ensuring its dispersal and survival, is discussed.